2023
DOI: 10.1111/apt.17739
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of diagnostic tests for bile acid diarrhoea

Christian Borup,
Lars Vinter‐Jensen,
Søren Peter German Jørgensen
et al.

Abstract: SummaryBackgroundBile acid diarrhoea is often missed because gold standard nuclear medicine tauroselcholic [75‐Se] acid (SeHCAT) testing has limited availability. Empirical treatment effect has unknown diagnostic performance, whereas plasma 7α‐hydroxy‐4‐cholesten‐3‐one (C4) is inexpensive but lacks sensitivity.AimsTo determine diagnostic characteristics of empirical treatment and explore improvements in diagnostics with potential better availability than SeHCAT.MethodsThis diagnostic accuracy study was part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, we recently reported the false positive rate of such an approach as high as 35% and such misclassification would dilute out differences between cases and controls. 24 Lastly, although we used nationwide registries, the number of patients with BAD and associated cancer events was relatively low. An expert opinion estimates a 1% prevalence of BAD by extrapolating data from cohorts of copyright.…”
Section: Discussionmentioning
confidence: 99%
“…However, we recently reported the false positive rate of such an approach as high as 35% and such misclassification would dilute out differences between cases and controls. 24 Lastly, although we used nationwide registries, the number of patients with BAD and associated cancer events was relatively low. An expert opinion estimates a 1% prevalence of BAD by extrapolating data from cohorts of copyright.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that current research has proposed a combination of fecal bile acid measurements and serum C4 measurements for diagnostic purposes [3,65]. A recent study revealed that the combination of C4 detection with ≥1.1 daily watery stools (Bristol type 6 and 7) had 70% (51-85%) sensitivity and 95% (83-99%) specificity, the logistic regression model including C4, the sum of measured stool bile acids and daily watery stools, had 77% (58-90%) sensitivity and 93% (80-98%) specificity, suggesting considerable improvements in the sensitivity of C4-based testing [66]. However, there is an urgent need to establish diagnostic criteria, which necessitates further in-depth research.…”
Section: Molecular Biomarkers Detectionmentioning
confidence: 99%
“…Moreover, optimization of measurement methods for fecal bile acid and serum C4, including sampling times, is necessary to enhance their accuracy and repeatability. Additionally, machine learning techniques and other approaches can be employed to develop models predicting the occurrence and severity of BAD based on results from fecal bile acid and serum C4 measurements with support from database algorithms [66,67].…”
Section: Molecular Biomarkers Detectionmentioning
confidence: 99%
“…Borup et al 10 conducted a study in 251 consecutive patients (without inflammatory bowel disease or microscopic colitis) undergoing 75 SeHCAT scanning. In this cohort, 38% had <10% retention (at least moderate BAD).…”
Section: Sensitivity Specificity Performance Versus Sechat Retention ...mentioning
confidence: 99%
“…The authors conducted a cross‐tabulation and receiver operating characteristics analysis, logistic regression and decision tree modelling of the diverse individual or combined tests relative to SeHCAT retention ≤10% as gold standard, using 60% of the cohort for model derivation and 40% for validation. The Table 1 10 provides performance characteristics of the diverse tests.…”
Section: Sensitivity Specificity Performance Versus Sechat Retention ...mentioning
confidence: 99%